Analisis Framing Headline Tentang Wacana Kenaikan Harga BBM Di Harian KOMPAS dan SOLOPOS Periode Maret 2012 - Herawati, Aprillia; Maharani Serikit, Poundra Swasty Ratu (KOMUNITAS, 2013)
Background of the research is authorâs interest with issue of increased price of fuel oil in which it became a popular discussion among people when the issue was starting to develop. The issue of fuel oil price upsurge running about March2012. The research uses framing analysis method by using Zhongdan Pan and Gerald M. KosickiÂ instruments. The headlines of Kompas and Solopos newspapers are then analyzed by using framing tool from Pan Konsicki consisting of four big structures, namely, syntax, script, thematic, and rhetoric.Â Findings of the research indicated that Kompas and Solopos newspaper have different frames about phenomenon of fuel oilÂ priceÂ upsurge.Â TheÂ differentÂ framesÂ usedÂ byÂ KompasÂ andÂ Solopos newspapersÂ inÂ framing newsÂ ofÂ theÂ phenomenonÂ discourseÂ wereÂ inÂ syntaxÂ aspect;Â especiallyÂ thoseÂ wereÂ relatedÂ with headline and informant.